INFLUENCE OF BRAND CHARACTERISTIC, COMPANY CHARACTERISTIC AND TRUST IN A BRAND TOWARD BRAND LOYALTY (STUDY OF TOLAK ANGIN SIDOMUNCUL CONSUMER IN YOGYAKARTA) - Prasojo Pribadi; Basu Swastha Dharmmesta (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Trust with a brand in pharmacy product has a strategic role in building consumer loyalty with that product. This research was done to understand factors that have influence in consumer loyalty with a pharmacy product. This research was correlation research using questionnaire as instrument that filled 175 respondents obtained by non-probability sampling method. Hypothesis test was done using simple regression and double regression. Hypothesis test result showed that brand competence, trust with the company and company reputation have positive influence in trust of a brand. Trust of a brand gives positive influence in brand loyalty. Brand characteristic and company characteristic have direct positive influence in brand loyalty. The bigger influence happen when trust of a brand act as mediator variable between brand characteristics and company characteristics with brand loyalty. Key words : brand loyalty, brand characteristics, company characteristics, Tolak Angin Sidomuncul herbal product.